Bradykinin/B2 receptor activation regulates renin in M‐1 cells via protein kinase C and nitric oxide. Issue 7 (3rd April 2017) - Lara, Lucienne S.; Bourgeois, Camille R. T.; El‐Dahr, Samir S.; Prieto, Minolfa C.
Abstract: In the collecting duct (CD), the interactions of renin angiotensin system (RAS) and kallikrein‐kinin system (KKS) modulate Na + reabsorption, volume homeostasis, and blood pressure. In this study, we used a mouse kidney cortical CD cell line (M‐1 cells) to test the hypothesis that in the CD, the activation of bradykinin B2 receptor (B2 R) increases renin synthesis and release. Physiological concentrations of bradykinin (BK) treatment of M‐1 cells increased renin mRNA and prorenin and renin protein contents in a dose‐dependent manner and increased threefold renin content in the cell culture media. These effects were mediated by protein kinase C (PKC) independently of protein kinase A (PKA) because B2 R antagonism with Icatibant and PKC inhibition with calphostin C, prevented these responses, but PKA inhibition with H89 did not modify the effects elicited by the B2 R activation. BK‐dependent stimulation of renin gene expression in CD cells also involved nitric oxide (NO) pathway because increased cGMP levels and inhibition of NO synthase with L‐NAME prevented it. Complementary renin immunohistochemical studies performed in kidneys from mice with conventional B2 R knockout and conditional B2 R knockout in the CD, showed marked decreased renin immunoreactivity in CD, regardless of the renin presence in juxtaglomerular cells in the knockout mice. These results indicate that the activation of B2 R increases renin synthesis and release by the CD cells through PKC stimulation and NO release, which support further the interactions between the RAS and KKS. Abstract : The B2 R activation increases renin synthesis and release in CD cells through PKC stimulation and NO release. This data was complementary confirmed in mice lacking the bradykinin B2 R that exhibit downregulation of CD renin, and that which further support the interactions between the RAS and KKS.